2016
DOI: 10.1103/physrevc.93.064325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ground-state deformation on isoscalar giant resonances inSi28

Abstract: Multipole strength distributions for isoscalar L ≤ 2 transitions in 28 Si have been extracted using 386-MeV inelastic α scattering at extremely forward angles, including 0• . Observed strength distributions are in good agreement with microscopic calculations for an oblate-deformed ground-state. In particular, a large peak at an excitation energy of 17.7 MeV in the isoscalar giant monopole resonance (ISGMR) strength is consistent with the calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(132 citation statements)
references
References 64 publications
10
122
0
Order By: Relevance
“…4 Keeping in mind an independent particle picture where nucleons are bound by an average one-body potential. Excitation Energy (MeV) 208 Pb(p,p') 208 Pb(γ,xn) 208 48 Ca(γ, abs) SENDAI (1987) 48 Ca(e,e'n) S-DALINAC (2000) 48 Ca(p,p') RCNP (2016) Figure 4: Left panel: photoabsorption cross section at forward angles (proportional to the strength function in good approximation corresponding to the IVGDR) in 208 Pb as measured in different experiments. Figure taken from Ref.…”
Section: Nuclear Response To Small Perturbationsmentioning
confidence: 99%
“…4 Keeping in mind an independent particle picture where nucleons are bound by an average one-body potential. Excitation Energy (MeV) 208 Pb(p,p') 208 Pb(γ,xn) 208 48 Ca(γ, abs) SENDAI (1987) 48 Ca(e,e'n) S-DALINAC (2000) 48 Ca(p,p') RCNP (2016) Figure 4: Left panel: photoabsorption cross section at forward angles (proportional to the strength function in good approximation corresponding to the IVGDR) in 208 Pb as measured in different experiments. Figure taken from Ref.…”
Section: Nuclear Response To Small Perturbationsmentioning
confidence: 99%
“…The parameter value of β = −1.9 was proposed in Ref. [40], and widely used for the analysis of inelastic alpha scattering [2,[4][5][6][7][8][9][10]13,20,25,28,29]. On the other hand, the parameter value of β = 0.0 means that the interaction is independent of the density of the target nucleus.…”
Section: A Optical-model Potential For the Elastic α Scattering And mentioning
confidence: 99%
“…Isoscalar giant monopole resonances (ISGMRs) and isoscalar giant dipole resonances (ISGDR) are extensively examined by the MDA for the inelastic α scattering [1][2][3][4][5][6][7][8][9][10]. The ISGMR and ISGDR strength distributions were successfully extracted from continuous excitation-energy spectra by the MDA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, interesting and promising experimental data were reported by the measurement of 28 Si(α,α ) 28 Si * inelastic scattering [57,58]. It was found that a couple of 0 + states above 9 MeV are strongly populated and were deduced to have large IS monopole transition strengths.…”
Section: M(i S0mentioning
confidence: 99%